Assessing the drought in the state of Ceará - Brazil: the relationship between drought, trophic state index, and anthropogenic pressure - Jefferson Hannover Faustino Magalhães; Francisco Judivan Celestino de Sousa; Carlos Eduardo Sousa Lima; Cleiton da Silva Silveira (Revista Brasileira de Ciências Ambientais)
The present study addressed the effects of water scarcity on the deterioration of water quality in 155 reservoirs located in the state of Ceará, Brazil, using the drought index SPI (standardized precipitation index) calculated for the accumulation time scales of 3, 6, and 12 months. Based on this, a comparison was made with the variations in the trophic state index of these reservoirs, between 2008 and 2021. The study pointed to the occurrence of an intense series of dry events between 2012 and 2018, highlighting the year 2013, when the SPI assumed a value of -2.43 identifying an extremely dry year. Also, during this period, the amount of water stored by the state’s reservoirs achieved only 8% of the total storage capacity, with the existence of eutrophic and hyper-eutrophic dams accounting for 68% of the total in 2016. In this context, it was observed that, during the transition from a dry to a wet period, the average trophic state index of the reservoirs tended to increase, rising from 62.1 (2008–2012) to 65.1 (2013–2017), before decreasing to 61.5 with the return of the wet period (2018–2021). In addition, to assess the influence of human activities on water quality, land use and occupation data from three basins in Ceará were analyzed. It was observed that the basin with the largest area occupied by agriculture experienced the most significant increases in total phosphorus and chlorophyll-a concentrations.